Effectiveness of Wish and Drive Method Education in Improving Knowledge and Participation in Cervical Cancer Screening Using Visual Inspection with Acetic Acid (VIA) among Women of Reproductive Age - Ni Wayan Ayu Puspita Dewi; Komang Ayu Henny Achjar; I Ketut Gama; Ketut Sudiantara; Suparji Suparji (Knowledge Dynamics, 2026)
Background: Cervical cancer remains one of the leading causes of mortality among women, particularly in developing countries, and can be detected early through Visual Inspection with Acetic Acid (VIA) screening. However, low knowledge and participation rates among women of reproductive age (WRA) remain major challenges. This study aimed to determine the effect of education using the wish and drive method on knowledge and participation in cervical cancer early detection. Methods: This study employed a quasi-experimental design with a pretest–posttest control group approach. A total of 60 respondents were selected using purposive sampling and divided into intervention and control groups. Data were collected using a structured questionnaire to assess knowledge and a checklist to measure participation in VIA screening. Data analysis was conducted using univariate and bivariate tests, including the Wilcoxon signed-rank test and Mann–Whitney U test. Results: The intervention group showed a significant increase in knowledge, with the proportion of “good” knowledge rising from 26.7% to 86.7%, while the control group experienced a decrease from 36.7% to 23.3%. Participation in VIA screening in the intervention group increased from 43.3% to 70%, compared to a slight increase in the control group from 40% to 43.3%. Statistical analysis indicated significant differences in both knowledge (p = 0.000) and participation (p=0.002) after the intervention. Conclusions: Education using the wish and drive method effectively improves knowledge and participation in cervical cancer early detection among WRA. This method is recommended for implementation in community-based health promotion programs to enhance screening uptake and preventive health behavior.